O5D.2 Occupational exposure of healthcare personnel to nitrous oxide in various pediatric specialty care units: an observational study. (April 2019) - Denis, Marie-Agnès; Pete-Bonneton, Charlotte; Riche, Benjamin; Cadot, Robert; Massardier-Pilonchery, Amélie; Iwaz, Jean; Charbotel, Barbara
Abstract : Objectives: Nitrous oxide (N2O) present in anesthetic mixtures (e.g., equimolar mix of oxygen and N2O, EMONO) has been found responsible for various toxicities, including genetic and reproductive toxicities. N2O-containing mixtures are widely used in pediatric care units where most healthcare providers (HCPs) are women of childbearing age. This motivated an investigation of occupational exposure to N2O in search for overexposure and overexposure factors in a pediatric hospital. Methods: This observational study concerned seven different units. On each of 34 HCPs, air samples were extracted by portable pumps and collected in Tedlar® bags. N2O was quantified by gas chromatography coupled to pulsed discharge ionization detection and infrared spectrometry. The data allowed calculating mainly the instantaneous exposure and the 8 hour time-weighted average (8h-TWA). Results: The exposure was four times higher in closed than in open treatment rooms and two times higher in case of use vs. non-use of EMONO. The exposure was significantly higher in junior vs. senior HCPs (by 12%) and higher during presumably short vs. presumably long procedures (by 20%). The mean 8h-TWAs were rather higher than the recommended exposure limit (25 ppm/8 hour) in emergency unit and in day hospital for thoracic and abdominal diseases. Overexposures represented 11% of all measurements but reached substantial levels (up to 3.5 times the recommended threshold). Conclusions: Overexposures to N2O were frequent during short-duration procedures. The causes of overexposure were insufficient air renewal and inappropriate equipment use. This calls for dedicated rooms, more efficient medical/nursing practices, proper training, and regular checks of gas levels.